1983
DOI: 10.1071/bi9830147
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Glucose into Lipid of Perirenal and Subcutaneous Adipocytes of Rats and Sheep: Influence of Insulin

Abstract: Adipocytes were prepared by collagenase digestion of perirenal and subcutaneous fat from rats and sheep and were incubated in vitro with various concentrations of glucose and insulin. The lipogenic rate of perirenal and subcutaneous adipocytes of rats showed a quadratic response to glucose concentration. The addition of 10 nM insulin increased lipogenesis, especially at low lipogenic rates. At constant glucose concentrations, insulin concentrations up to 50 nM stimulated lipogenesis a similar amount in adipocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Logarithmic transformation (base e) of the depilation force and NAT activity data (Figs 1, 2 a), was carried out to stabilize variances, normalize the data and so validate the tests of hypotheses (see e.g. Broad, Sedcole & Ngan, 1983). Depilation force clearly follows a circadian rhythm in ewes and wethers ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Logarithmic transformation (base e) of the depilation force and NAT activity data (Figs 1, 2 a), was carried out to stabilize variances, normalize the data and so validate the tests of hypotheses (see e.g. Broad, Sedcole & Ngan, 1983). Depilation force clearly follows a circadian rhythm in ewes and wethers ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, lipogenic activity is greater in subcutaneous adipose tissue than in perirenal adipose tissue (Hood and Allen, 1973;Loveday and Dikeman, 1980). In sheep, however, perirenal adipocytes were more active in in vitro lipogenesis than subcutaneous adipocytes (Broad et al, 1983). Also with sheep, in vivo conversion of acetate to long-chain fatty acids was greater in perirenal than subcutaneous adipose tissue (Ingle et al, 1972b).…”
Section: Effect Of Anatomical Locationmentioning
confidence: 96%
“…Hood and Allen (1975) suggested that cytosolic water becomes limiting when fat cells are very large. In sheep, Broad et al (1983) found lipogenesis to increase with cell volume only in perirenal adipose tissue.…”
Section: Effect Of Cell Volumementioning
confidence: 97%